Studies on Schismatoglottideae (Araceae) of Borneo XXXVIII: three novel Schismatoglottis species, and notes on the Schismatoglottis Asperata Complex - Wong, Sin Yeng; Boyce, P.C (Taylor & Francis Group, LLC, 2014)
Schismatoglottis crypta P.C. Boyce & S.Y. Wong, Schismatoglottis shaleicola P.C. Boyce & S.Y. Wong, and Schismatoglottis tegorae P.C. Boyce & S.Y. Wong are described as taxonomically novel species assigned to a newly circumscribed Asperata Complex. Schismatoglottis crypta and S. tegorae are facultative rheophytes most similar to Schismatoglottis jelandii P.C. Boyce & S.Y. Wong; S. shaleicola is a mesophytic species reminiscent of Schismatoglottis sejuncta A. Hay. A key to the species of the Schismatoglottis Asperata Complex is provided, and most species are figured from living plants.